Early Mesopotamia - Postgate, Nicholas, author.
1 online resource (392 pages)
Keywords: The roots of our modern world lie in the civilization of Mesopotamia, which saw the development of the first urban society and the invention of writing. The cuneiform texts reveal the technological and social innovations of Sumer and Babylonia as surprisingly modern, and the influence of this fascinating culture was felt throughout the Near East. Early Mesopotamia gives an entirely new account, integrating the archaeology with historical data which until now have been largely scattered in specialist literature.